Iron deficiency prevalence and dietary patterns by school district in Istanbul - (:unkn) unknown (WILEY, 2007)
Introduction The aim of this study was to record the prevalence of iron deficiency (serum ferritin concentration < 15 mu g L-1) among schoolchildren and identify possible factors related to the development of this medical condition. Materials and methods The study population consisted of 504 schoolchildren attending three primary schools, located in two districts of Istanbul with higher and lower socio-economic level (SEL) respectively. Certain biochemical and haematological indices of iron status were measured. Dietary intake was estimated using the 24-h recall technique and a food frequency questionnaire. Results The prevalence of iron deficiency in the lower SEL school district was twice that of the higher SEL school district (42% and 21.2% respectively). Furthermore, the levels of serum ferritin, mean corpuscular volume, mean corpuscular haemoglobin (all P < 0.001) and mean corpuscular haemoglobin concentration (P = 0.016) were higher for students in the higher than in the lower SEL school district. Consumption of tea, cola beverages and dairy products was more frequent by children living in the lower than in the higher SEL school district. Furthermore, consumption of red meat and citrus fruits was less frequent by boys in the lower than in the higher SEL school district. Conclusions Iron deficiency was more prevalent among children from the lower SEL school district. Different patterns in the consumption of foods and beverages that inhibit or enhance intestinal iron absorption between children in the two school districts could provide some explanation for the observed differences in the prevalence of iron deficiency.
Keywords: children; diet; iron deficiency; school district; Turkey; ARAL SEA REGION; ANEMIA; BIOAVAILABILITY; SCHOOLCHILDREN; ADOLESCENTS; ABSORPTION; VALIDITY; CHILDREN